Do public employment and training programs work? - Carolyn J. Heinrich; Peter R. Mueser; Kenneth R. Troske; Kyung-seong Jeon; Daver C. Kahvecioglu (IZA Journal of Labor Economics, 2013)
We estimate impacts on earnings and employment of the two primary adult workforce support and training programs under the U.S. Workforce Investment Act (WIA) using administrative data on 160,000 participants from 12 states for up to four years following program entry. We find that participants in the WIA Adult program, who typically enter with poor work histories, realize improved employment levels and increased average quarterly earnings of several hundred dollars. Earnings gains for Dislocated Worker program participants are appreciably smaller, although these participants do experience employment gains.We document and attempt to explain the recent decline in employment dynamics in the U.S. We have four major empirical findings. First, each measure exhibits a 'stair step' pattern, with the declines concentrated in recessions and little increase during subsequent expansions. Second, changes in the composition of workers and businesses can explain only a small amount of the decline. Third, any explanation for the decline in job creation and job destruction will account for no more than one-third of the decline in hires and separations. Fourth, the decline in hires and separations is driven by the disappearance of short-duration jobs.
Keywords: I38; J08; J24; 330; Job training; Program evaluation; Workforce investment act; Matching